Institutional Effectiveness of Tax Debt Collection in Increasing State Revenue - Herianto Herianto (Interdiciplinary Journal and Hummanity (INJURITY), 2024)
Tax debt collection is an important element for optimizing state revenue, but until now it has not run optimally. The process of collecting tax debts in Indonesia is often long and complicated. Tax collection faces obstacles such as short billing expirations, regulatory complexity, and unwieldy sanctions. The solution to this challenge involves improving regulations, increasing taxpayer awareness, strengthening institutions, and mitigating external factors affecting tax payment. This research is expected to provide an evaluation of the effectiveness of institutional mechanisms in enhancing tax debt collection for state revenue in Indonesia and an analysis of the current institutional regulations governing tax debt collections, providing insights into potential areas for reform and improvement.